Plants of the annonaceae traditionally used as antimalarials: A review - Frausin, Gina; Lima, Renata Braga Souza; Hidalgo, Ari de Freitas; Maas, Paul J.M.; Pohlit, Adrian Martin (Revista Brasileira de Fruticultura, 2014)
Species of the Annonaceae family are used all over the tropics in traditional medicine in tropical regions for the treatment of malaria and other illnesses. Phytochemical studies of this family have revealed chemical components which could offer new alternatives for the treatment and control of malaria. Searches in scientific reference sites (SciFinder Scholar, Scielo, PubMed, ScienceDirect and ISI Web of Science) and a bibliographic literature search for species of Annonaceae used traditionally to treat malaria and fever were carried out. This family contains 2,100 species in 123 genera. We encountered 113 articles reporting medicinal use of one or more species of this family including 63 species in 27 genera with uses as antimalarials and febrifuges. Even though the same species of Annonaceae are used by diverse ethnic groups, different plant parts are often chosen for applications, and diverse methods of preparation and treatment are used. The ethanol extracts of Polyalthia debilis and Xylopia aromatica proved to be quite active against Plasmodium falciparum in vitro (median inhibition concentration, ICinf50/inf < 1.5 μg/mL). Intraperitoneal injection of Annickia chlorantha aqueous extracts (cited as Enantia chlorantha) cleared chloroquine-resistant Plasmodium yoelii nigeriensis from the blood of mice in a dose-dependant manner. More phytochemical profiles of Annonaceous species are required; especially information on the more commonly distributed antimalarial compounds in this family.
Plantas da familia annonaceae tradicionalmente usadas como antimaláricos: Uma revisão
Keywords: Annickia Chlorantha; Annonaceae; Mus; Plasmodium Falciparum; Plasmodium Yoelii Nigeriensis; Polyalthia Debilis; Xylopia